Stratifikasi Periwayat Hadis menurut Ibn al-Jawzi (w. 597 H) dalam kitab al-Hats ‘ala Hifz al-‘Ilm wa Dzikr Kibar al-Huffaz - Kinkin Syamsudin; M. Dede Rodliyana (Prodi Ilmu Hadis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2021)
Hadith scholars have formulated a special designation or title pinned to the narrators of hadith hierarchically according to the large number of narrations they have memorized. The use of this title shows that the stratification among the narrators of hadith is true. So this paper aims to explain the concept of stratification in the hadith musthalahat and prove it empirically through the study of other books. By using the literature study method and through the content analysis approach, it can be seen that in the book al-Hats ‘ala Hifz al-‘Ilm wa Dzikr Kibar al-Huffaz, Ibn al-Jawzi clearly describes several profiles of hadith narrators complete with notes on the number of memorization the hadith they have. This is evidence that the concept of stratification formulated by hadith scholars is consistent with the discovery of the facts that every hadith narrator memorized a number of traditions.